The Designation of Variable Exhaust Nozzle for Micro Gas Turbine - Mohd Yasin, Muhammad Badrul Amin; Salleh, Hamidon (Research Progress in Mechanical and Manufacturing Engineering, 2023)
UAVs are a fast increasing commercial aviation activity that will have a substantial economic influence in the near future. The usage of tiny UAVs in civic and commercial activities such as photography, wildlife research and survey, agriculture surveying and mapping, and others has increased business demand for UAVs. This market’s rapid expansion will be accompanied by improvements in functionality such as increased durability, decreased noise and emissions, and expanded mission range, among other things.